Linear-type carbazoledioxazine-based organic semiconductors: the effect of backbone planarity on the molecular orientation and charge transport properties. Issue 18 (13th March 2018) - Otsuka, Rikuo; Wang, Yang; Mori, Takehiko; Michinobu, Tsuyoshi
Abstract : A linear-type dibromocarbazoledioxazine (CZ ) derivative and its two polymers are newly designed and synthesized. Structure–property relationship studies reveal thatPCZTT shows a four times higher hole mobility thanPCZT . Abstract : We report the synthesis of a linear-type dibromocarbazoledioxazine (CZ ) derivative as a new precursor for semiconducting polymers. The chemical structures of theCZ unit and its polymers with thiophene or thienothiophene spacers (namely, PCZT andPCZTT ) were fully characterized.PCZT andPCZTT possessed similar medium optical band gap ( E optg) and electrochemical band gap ( E cvg) of around 1.70 eV estimated from the onset absorption and electrochemical redox potentials of the thin films, respectively. Computational density functional theory (DFT) calculations suggested that the backbone of thePCZT might be highly twisted, while that ofPCZTT could be very planar. The effect of different backbone geometries on the charge–transport properties was studied by using thin film transistors (TFTs). The TFT device based onPCZTT showed a four times higher hole mobility as compared to that based onPCZT . The superior TFT performances ofPCZTT were reasonably attributed to its edge-on backbone packing orientations toward the Si substrate revealed by the grazing-incidence wide-angle X-ray scattering (GIWAXS), which was favorable for in-plane charge transport in the TFT devices.